Spletna aplikacija svojilni pridevniki iz prevzetih priimkov (SPiPP) kot vir za raziskave govora : Irena Stramljič Breznik (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Web Application Possessive Adjectives from Adopted Personal Proper Names (SPiPP) as a Resource for Speech Research. This article discusses why the formation of possessive adjectives from adopted personal proper names is one of the most difficult problems in the Slovene language despite numerous orthographic guidelines in current and emerging orthographic manuals. As an alternative, we present the online tool SPiPP, which offers help in the formation of such adjectives by providing spelling, pronunciation and rules in one place. At the same time, the SPiPP application can also be used as a language resource for the further development of speech aids. To illustrate this usefulness, 60 randomly selected French surnames from the application were tested with the Slovene speech synthesiser eBralec. The aim of the test was to use the currently available audio recordings and the rules on the relationships between letters and sounds of foreign languages and the Slovene language to stimulate a gradual further development of eBralec, so that it would include the pronunciation of foreign proper nouns and their forms adapted to Slovene.